2006
DOI: 10.1128/jcm.44.3.992-998.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genotype 1 and Genotype 2 Bovine Noroviruses Are Antigenically Distinct but Share a Cross-Reactive Epitope with Human Noroviruses

Abstract: The bovine enteric caliciviruses Bo/Jena/1980/DE and Bo/Newbury2/1976/UK represent two distinct genotypes within a new genogroup, genogroup III, in the genus Norovirus of the family Caliciviridae. In the present study, the antigenic relatedness of these two genotypes was determined for the first time to enable the development of tests to detect and differentiate between both genotypes. Two approaches were used. First, cross-reactivity was examined by enzyme-linked immunosorbent assay (ELISA) using recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 38 publications
(65 reference statements)
4
40
1
7
Order By: Relevance
“…The low value of Spearman's rank correlation indicated a moderate cross-reactivity of antibodies against NoV GIII to NoV GI and GII, but this alone could not explain the observed seroreactivity to bovine VLPs. This is similar to other studies which show limited cross-reactivity between human and bovine NoV strains (14,15,21,34). The differences in the prevalence rates of antibody to the VLPs tested likely indicate different levels of exposure to these viruses, with significant differences in exposure between human genogroups and bovine NoVs.…”
supporting
confidence: 75%
“…The low value of Spearman's rank correlation indicated a moderate cross-reactivity of antibodies against NoV GIII to NoV GI and GII, but this alone could not explain the observed seroreactivity to bovine VLPs. This is similar to other studies which show limited cross-reactivity between human and bovine NoV strains (14,15,21,34). The differences in the prevalence rates of antibody to the VLPs tested likely indicate different levels of exposure to these viruses, with significant differences in exposure between human genogroups and bovine NoVs.…”
supporting
confidence: 75%
“…Several cross-reactive MAbs have been described for noroviruses, and epitopes for most of them have been mapped within the most conserved regions of the norovirus capsid protein (C-terminal P or S domain). As suggested previously, cross-reactive MAbs could potentially be used in diagnostic assays (3,24,36,46,51); however, Oliver et al (45) described a cross-reactive MAb that recognized a linear epitope in the S domain of the VLPs from bovine noroviruses that did not detect native virions in fecal samples from experimental animals. They proposed that because the S domain forms the innermost domain of the capsid, the epitope is not accessible in native virions.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-reactive MAbs have been identified, and most of them have been mapped to the S domain or the C-terminal region of the P1 domain (3,4,35,45,46,51,65,66). It has been reported that certain MAbs block the interaction of VLPs with cells or synthetic HBGA (38,43), and two HBGA-blocking sites were recently mapped (11,37).…”
mentioning
confidence: 99%
“…Also, antibodies to marine and terrestrial vesiviruses and vesivirus genome sequences have been detected in blood donors in the United States [13]. Animal enteric caliciviruses genetically related to human NoVs and SaVs have been detected in pigs and cows [2,[14][15][16][17][18][19][20][21]. Antibodies to human NoV have been detected in pigs and antibodies to bovine NoV have been detected in humans [22,23].…”
Section: Introductionmentioning
confidence: 94%